Cell Cycle-Dependent Flagellar Disassembly in a Firebug Trypanosomatid Leptomonas pyrrhocoris - He, Cynthia Y; Singh, Adarsh; Yurchenko, Vyacheslav (mBio, 2019)
Current understanding of flagellum/cilium length regulation focuses on a few model organisms with flagella of uniform length. Leptomonas pyrrhocoris is a monoxenous trypanosomatid parasite of firebugs. When cultivated in vitro, L. pyrrhocoris duplicates every 4.2 ± 0.2 h, representing the shortest doubling time reported for trypanosomatids so far. Each L. pyrrhocoris cell starts its cell cycle with a single flagellum. A new flagellum is assembled de novo, while the old flagellum persists throughout the cell cycle. The flagella in an asynchronous L. pyrrhocoris population exhibited a vast length variation of ∼3 to 24 μm, casting doubt on the presence of a length regulation mechanism based on a single balance point between the assembly and disassembly rate in these cells. Through imaging of live L. pyrrhocoris cells, a rapid, partial disassembly of the existing, old flagellum is observed upon, if not prior to, the initial assembly of a new flagellum. Mathematical modeling demonstrated an inverse correlation between the flagellar growth rate and flagellar length and inferred the presence of distinct, cell cycle-dependent disassembly mechanisms with different rates. On the basis of these observations, we proposed a min-max model that could account for the vast flagellar length range observed for asynchronous L. pyrrhocoris. This model may also apply to other flagellated organisms with flagellar length variation.IMPORTANCE Current understanding of flagellum biogenesis during the cell cycle in trypanosomatids is limited to a few pathogenic species, including Trypanosoma brucei, Trypanosoma cruzi, and Leishmania spp. The most notable characteristics of trypanosomatid flagella studied so far are the extreme stability and lack of ciliary disassembly/absorption during the cell cycle. This is different from cilia in Chlamydomonas and mammalian cells, which undergo complete absorption prior to cell cycle initiation. In this study, we examined flagellum duplication during the cell cycle of Leptomonas pyrrhocoris With the shortest duplication time documented for all Trypanosomatidae and its amenability to culture on agarose gel with limited mobility, we were able to image these cells through the cell cycle. Rapid, cell cycle-specific flagellum disassembly different from turnover was observed for the first time in trypanosomatids. Given the observed length-dependent growth rate and the presence of different disassembly mechanisms, we proposed a min-max model that can account for the flagellar length variation observed in L. pyrrhocoris.
Keywords: Animals; buněčný cyklus; flagella; Protozoan Proteins; protozoální proteiny; teoretické modely; zvířata; hmyz; Trypanosomatina; Models, Theoretical; Insecta; Flagella; Cell Cycle